2011
DOI: 10.1177/0003319711427392
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet in Relation to Ischemic Stroke Nonfatal Events in Nonhypercholesterolemic and Hypercholesterolemic Participants

Abstract: The aim of the present work was to evaluate the association between adherence to the Mediterranean diet and the development of ischemic stroke according to cholesterol levels. During 2009-2010, 500 participants were enrolled; 250 were consecutive patients (77 ± 9 years, 55.6% men) with a first ischemic stroke and 250 population-based, control participants, matched to the patients by age and sex. Sociodemographic, clinical, dietary, and other lifestyle characteristics were measured. Adherence to the Mediterrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Some epidemiological studies have also examined the association between a MDS and the risk of stroke. Among these, some (31,38,39) found an inverse association, while others did not (17,40) . Moreover, a recent paper has found an inverse association between adherence to a Mediterranean-like diet and total cerebrovascular disease (41) .…”
Section: Discussionmentioning
confidence: 97%
“…Some epidemiological studies have also examined the association between a MDS and the risk of stroke. Among these, some (31,38,39) found an inverse association, while others did not (17,40) . Moreover, a recent paper has found an inverse association between adherence to a Mediterranean-like diet and total cerebrovascular disease (41) .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the EPIC (European Investigation into Cancer and Nutrition) provided important evidence, based on analyses on large numbers of subjects [57]. Along these new approaches, several other concepts have emerged such as the protective role of the Mediterranean diet on renal function [58] and on the levels of serum uric acid [59], on weight control [60], on metabolic syndrome [61] and on developing ischaemic stroke [62]. Moreover, the study of the Mediterranean diet stimulated important comparative procedures between the a priori and the a posteriori approach for the definition of dietary patterns [63].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to CVD, there are several studies analyzing the effects of a priori 264 defined MDP, that found a cardio-protective effect of this DP [23,24]. However, different 265 28 country-specific DP have been described in Mediterranean populations and these results 266 should be interpreted with caution.…”
Section: Discussion 224mentioning
confidence: 99%